Control of a Shunt-Series Modular Multilevel Converter for Low-Frequency Ac Transmission Systems - Diaz-Diaz, M; Pizarro-Jimenez, P; Rajendran, S (Institute of Electrical and Electronics Engineers Inc., 2022)
Low-frequency AC transmission systems have been suggested as a suitable option for high-power transmission as they offer advantages compared to conventional high-voltage AC or high-voltage DC transmission systems. However, this application requires direct AC-AC conversion at high power-voltage ratios. In the context of high-power converters, several publications have been made on the Modular Multilevel Cascaded Converters, characterised as topologies with high voltage levels, full scalability, increased flexibility of control, and both high power and energy quality. Therefore, this paper studies a new topology for a Low-Frequency AC transmission system referred to as Shunt-Series Modular Multilevel Converter, a decoupled control strategy is proposed and simulation results are presented and analysed. © 2022 IEEE.